Dermatologia comparativa: fibroqueratoma digital adquirido Comparative dermatology: acquired digital fibrokeratoma - Roberto Rheingantz da Cunha Filho (Sociedade Brasileira de Dermatologia, 2008)
Demonstra-se quadro característico de fibroqueratoma digital adquirido em trabalhadora rural de 42 anos de idade, que se compara a corno de rinoceronte. It is presented a case of a 42 year-old white female farmer with the classical feature of acquired digital fibrokeratoma, which is compared to rhinoceros horn.